Multi-modal fMRI and TMS follow-up study of motor cortical stroke caused by hyaluronic acid filler: A case report - Tang, Xinwei; Yu, Qiurong; Guo, Miao; Liu, Fan; Pan, Yongquan; Zhou, Jingyuan; Zou, Yue; Wu, Cheng; Yu, Kewei; Fan, Mingxia; Sun, Limin (Frontiers in Neurology, 2022)
Background Blindness and stroke resulting from hyaluronic acid (HA) fillers are not frequently reported complications. Reports on stroke recovery after HA injection are limited. In the current study, the recovery process, task-based functional magnetic resonance imaging (fMRI), diffusion tensor imaging (DTI), and neurophysiological changes of a patient with monocular blindness and ipsilateral motor cortical stroke after forehead injection of HA are explored. Case-report The study comprised a 34-year-old female patient who presented with left eye blindness and a stroke after receiving an HA injection a month before admission. The lesion was mainly limited to the left precentral gyrus, and the patient had pure arm monoparesis. For 3 weeks, the patient received conventional rehabilitation treatments and ten sessions of repetitive transcranial magnetic stimulation (rTMS) intervention. Clinical assessments, neurophysiological evaluation, task-based fMRI, and DTI examinations were conducted to assess her motor improvement and the possible neuro mechanism. Clinical rehabilitation impact The patient's right upper limb motor function was almost completely restored after receiving rehabilitation therapy. However, the vision in her left eye did not show significant improvement. The neurophysiological evaluation showed partial recovery of the ipsilesional motor evoked potentials (MEPs). DTI results showed that the ipsilesional corticospinal tract (CST) was intact. Task-based fMRI results indicated that the activation pattern of the affected hand movement was gradually restored to normal. Conclusion A case of good motor recovery after stroke due to HA injection with a lesion mainly restricted to the precentral gyrus but without CST damage is presented in the current study. Further studies should be conducted to explore the efficacy and the mechanisms of rehabilitation and neuromodulation approaches to motor cortical stroke.